2020
DOI: 10.7755/fb.118.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Updated reproductive parameters for the shortfin mako (Isurus oxyrinchus) in the North Atlantic Ocean with inferences of distribution by sex and reproductive stage

Abstract: the target species, they are frequently retained for their meat, fins, and jaws (Casey and Kohler, 1992; Babcock and Nakano, 2008). Although the species has long been considered vulnerable to overexploitation because of its late age at maturity, low reproductive potential, and commercial value (Dulvy et al., 2008; Cortés et al., 2010), catch levels were considered sustainable (ICCAT 2). However, the results of an electronic tagging study conducted in 2013-2015 2 ICCAT (International Commission for the Conserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…For shortfin mako, Vooren et al (2005) and Costa et al (2002) reported the presence of neonates and pregnant females off southern Brazil. Moreover, the hypothesis of a nursery ground off Northwest Africa and Portugal is supported by the occurrence of neonate and young-of-the-year shortfin makos reported in Maia et al (2007) and Natanson et al (2020). Here, the presence of two neonates tagged off the Canary archipelago (tag IDs 62420 and 62621) reinforces the importance of this region for parturition.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…For shortfin mako, Vooren et al (2005) and Costa et al (2002) reported the presence of neonates and pregnant females off southern Brazil. Moreover, the hypothesis of a nursery ground off Northwest Africa and Portugal is supported by the occurrence of neonate and young-of-the-year shortfin makos reported in Maia et al (2007) and Natanson et al (2020). Here, the presence of two neonates tagged off the Canary archipelago (tag IDs 62420 and 62621) reinforces the importance of this region for parturition.…”
Section: Discussionsupporting
confidence: 68%
“…The vast majority of analyzed tracks belong to juvenile sharks of both sexes; only two mature sharks were monitored. These sharks were presumed to be mature based on published 50% size-at-maturity data (males: 182 cm FL, females: 280 cm FL; Natanson et al, 2020). Both were male, tagged in the Southwest (tag ID 157376) and Central (tag ID 167207) Atlantic regions and followed the general trend to move within/toward the continental shelf.…”
Section: Horizontal Movements and Spatial Distributionmentioning
confidence: 99%
“…Eight of the mako sharks were tagged >40 nautical miles offshore from Port Aransas, and one was tagged from shore along the Padre Island National Seashore, Texas. The five males (167-218 cm FL) were mature or nearing maturity, and all four females (282-361 cm FL) were classified as mature based on published 50% size-at-maturity data (males: 182 cm, females: 280 cm; Natanson et al, 2020). Two females had recent (i.e., fresh with no healing or scarring) bite marks anterior to the dorsal fin at capture which could suggest mating or fighting behaviors were occurring (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The same pattern exists in other lamniforms, with females maturing later than males (e.g. Isurus oxyrinchus (Natanson et al ., 2020), Alopias superciliosus (Fernandez-Carvalho et al ., 2015 b ), Alopias vulpinus (Natanson & Gervelis, 2013)).…”
Section: Discussionmentioning
confidence: 99%